2022
DOI: 10.3390/vetsci9110628
|View full text |Cite
|
Sign up to set email alerts
|

Does TLS Exist in Canine Mammary Gland Tumours? Preliminary Results in Simple Carcinomas

Abstract: Neoplastic progression is influenced by the expression of tumour antigens that activate an anti-tumour immune response. Human medical studies show that this body defence is carried out in secondary lymphoid organs (SLOs) but also directly in the tumour through organized cellular aggregates that are called tertiary lymphoid structures (TLSs). However, their occurrence has different meanings in different tumour types. For example, the presence of TLSs in breast cancer is associated with the most aggressive subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
2
0
0
Order By: Relevance
“…Nevertheless, the greater positivity was concentrated near TLSs. In a previous study, we found TLSs were often located near or around vessels with emboli, so we hypothesized that they could be involved in the metastatic process, as already reported in human medicine [61,68]. In the same way, HLMs could have a potential metastatic role.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Nevertheless, the greater positivity was concentrated near TLSs. In a previous study, we found TLSs were often located near or around vessels with emboli, so we hypothesized that they could be involved in the metastatic process, as already reported in human medicine [61,68]. In the same way, HLMs could have a potential metastatic role.…”
Section: Discussionsupporting
confidence: 52%
“…Inflammatory cells can be organized in conspicuous groups of only lymphocytes (TILs) or in more complex structures of mixed populations, simulating lymphoid tissues (TLSs). In canine mammary tumors, as in breast cancer, TLSs can be described with different patterns of organization and are characterized by the presence of HEVs [61]. In this study, conspicuous groups of HLMs were located in the marginal areas of TILs or TLSs and were positive for VEGF, suggesting that they also have an angiogenic role in the development of HEVs.…”
Section: Discussionsupporting
confidence: 49%